VD_FINDINFO Décision / 2012 / 603 vom 25. April 2012 - VD Tribunal cantonal (2012)
NON-LIEU, CLASSEMENT DE LA PROCÉDURE, FRAIS JUDICIAIRES, INDEMNITÉEN GÉNÉRAL | 319 CPP (CH), 393 al. 1 let. a CPP (CH), 427 al. 2 CPP (CH), 432 CPP (CH)